Comparative Study of Allama Iqbal’s Urdu and Persian Composition of ode - Dr. Satar Khan Khattak (دریافت)
Allama Muhammad Iqbal started his poetry from Urdu ode or amatory verses. But very soon he started his poetry in Persian. Iqbal realized that the skirt of Urdu language is very narrow for his ideas and thoughts. He recognized that Urdu is a young inexperienced language. Urdu is spoken, written and reading in a limited part of the subcontinent. On the other hand person is an old and experienced language of the world and is spoken, written and reading in a vast part of the Muslim world. Persian language keeps the most valuable assets of poetry and prose. The Persians odes of Allama Iqbal are found in Piyam-e-mashriq and Zaboor-e-Ajam.  Some Urdu odes of Iqbal are found in Bang-e-Dara and Zarb-e-kaleem, but the most important odes are found in his famous book of Urdu poetry named as Bal-e-jibreel. This collection of poems by Allama Iqbal is very important, because what is clearly stated in his Persian odes, is what is indicated in Bal-e-Jibreel.  The first part of Bal-e-Jibreel consists of ghazals. Essentially, these ghazals portray the same meaning that the Persian ghazals imply. However, the experimental writing of these ghazals, the sheer talent employed in this book are as climactic in terms of poetry.